2021
DOI: 10.1038/s41598-021-96869-5
|View full text |Cite
|
Sign up to set email alerts
|

TANC1 methylation as a novel biomarker for the diagnosis of patients with anti-tuberculosis drug-induced liver injury

Abstract: We aimed to elucidate the differences in genomic methylation patterns between ADLI and non-ADLI patients to identify DNA methylation-based biomarkers. Genome-wide DNA methylation patterns were obtained using Infinium MethylationEPIC (EPIC) BeadChip array to analyze 14 peripheral blood samples (7 ADLI cases, 7 non-ADLI controls). Changes in the mRNA and DNA methylation in the target genes of another 120 peripheral blood samples (60 ADLI cases, 60 non-ADLI controls) were analyzed by real-time polymerase chain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…TANC1 has an ankyrin repeat (AR) domain that participates in many cell functions, especially tumorigenesis ( Yang et al, 2019 ). Through Ingenuity Pathway Analysis (IPA), genes regulated by TANC1 were enriched in hepatic inflammation and HCC ( Wu et al, 2021 ). ALKBH7, a mitochondrial ketoglutarate dioxygenase, decreases ROS formation to regulate programmed necrosis ( Meng et al, 2019 ; Kulkarni et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…TANC1 has an ankyrin repeat (AR) domain that participates in many cell functions, especially tumorigenesis ( Yang et al, 2019 ). Through Ingenuity Pathway Analysis (IPA), genes regulated by TANC1 were enriched in hepatic inflammation and HCC ( Wu et al, 2021 ). ALKBH7, a mitochondrial ketoglutarate dioxygenase, decreases ROS formation to regulate programmed necrosis ( Meng et al, 2019 ; Kulkarni et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria for the case group included liver injury after 2 months of treatment with anti‐TB drugs. The inclusion criteria for the control group included the absence of liver injury after 2 months of anti‐TB drug treatment and a match with patients in the case group in terms of age (<5 years difference), sex and therapeutic regimen (daily S(E)HRZ: S, streptomycin; E, ethambutol; H, isoniazid, R, rifampicin; Z, pyrazinamide) 16,17 …”
Section: Methodsmentioning
confidence: 99%
“…Hepatotoxicity due to anti‐TB drug treatment was not only based on the liver enzyme results, according to the criteria of the American Thoracic Society (ATS), but also took into account the diagnostic criteria developed by the Center for Drug Re‐evaluation (CDR) of the Chinese State Food and Drug Administration, as well as various previous definitions. Specifically, ADLI patients need to meet one of the following criteria 17 : (1) an increase in serum alanine aminotransferase (ALT) or aspartate aminotransferase (AST), which is over threefold the upper limit of normal (ULN) in the presence of liver injury symptoms; (2) an increase in total bilirubin (TBIL) that is over twofold the ULN in the presence of liver injury symptoms; (3) a fivefold increase in the ULN of serum ALT, AST or TBIL with or without liver injury symptoms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since epigenetics can bridge the gaps between the host, M. tuberculosis , and the environment, it might have great potential in predicting TB development. DNA methylation is the most widely studied epigenetic marker, and cytosine-guanine dinucleotide (CpG) methylation is central to many biological processes and human diseases ( 11 14 ). Previous studies reported that varied DNA methylation might be associated with TB risk ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%